Libras’s discipline on teacher training: challenges for the creation of bilingual educational spaces (Práxis Educativa, 2017)
In the selected field of study, it’s important to investigate whether the Libras discipline offer constitutes a formative and oriented space to bilingual educational consolidation according to Decree nº 5.626/05. The analysis of online available documents allowed to identify 19 courses that offered disciplines about bilingual education policies for the deaf. Among these courses 22 disciplines was found. Supported by content analysis, the data were organized in three categories: a) Libras teaching; b) Content about Libras; and c) Public Policies and Fundamentals of deaf education. Results shown that Libras discipline has been configured as a possibility of diffusion and teaching of this language modality, in the mentioned courses. Overall that the offer will contributes to fade away the misunderstanding of deaf schooling in the bilingual perspective. Keywords: Teacher training courses. Brazilian Sign Language. bilingual education policies.